The roles of HCV core protein and its binding host factor in virus assembly and release - Izumida, Kyo; Morita, Eiji (Frontiers in Virology, 2024)
Hepatitis C virus (HCV) is a well-known virus that causes liver diseases such as liver cirrhosis and hepatocellular carcinoma. For several decades, numerous studies have been conducted to unravel the life cycle and molecular mechanisms of this virus with the aim of developing strategies to combat diseases caused by its infection. In this review, we summarize HCV assembly to budding, focusing on one of the structural proteins, the core, a viral capsid that binds both the viral genome and host membrane, along with the core-interacting host partners. The HCV core matures in the endoplasmic reticulum (ER), localizes at the lipid droplet (LD), and shuttles between the LD and ER to form viral particles. This process is controlled by many host factors known to binds core proteins, such as diacylglycerol acyltransferase-1 (DGAT-1), Rab18, μ subunit of the clathrin adaptor protein complex 2 (AP2M1), nuclear pore complex protein 98 (Nup98), Cortactin, group IVA phospholipase A2 (PLA2G4A) etc. Virion budding is thought to involve contributions from endosomal sorting complexes required for transport (ESCRT), similar to other envelope viruses. We delved into potential perspectives to enhance our understanding of the HCV mechanism by drawing insights from existing studies.